Chemoenzymatic Approach to Optically Active 4‐Hydroxy‐5‐alkylcyclopent‐2‐en‐1‐one Derivatives: An Application of a Combined Circular Dichroism Spectroscopy and DFT Calculations to Assignment of Absolute Configuration. Issue 6 (1st May 2014) - Frelek, Jadwiga; Karchier, Michał; Madej, Daria; Michalak, Karol; Różański, Paweł; Wicha, Jerzy
ABSTRACT A series of representative optically active derivatives of 4‐hydroxy‐5‐alkylcyclopent‐2‐en‐1‐one were prepared from the respective 2‐furyl methyl carbinols via the Piancatelli rearrangement followed by the enzymatic kinetic resolution of racemates. Applicability of chiroptical methods (experimental and calculated electronic circular dichroism [ECD] and vibrational circular dichroism [VCD] spectra) to determine the absolute configuration of both stereogenic centers in 4‐hydroxy‐5‐methylcyclopent‐2‐en‐1‐one was demonstrated. It was also demonstrated that the concurrent application of ECD and VCD spectroscopy can be used for the determination of the configuration of two stereogenic centers. Chirality 26:300–306, 2014. © 2014 Wiley Periodicals, Inc.